Pengembangan Bahan Ajar Aljabar Linier Berbasis Nilai-nilai Keislaman dengan Pendekatan Saintifik - Pratiwi, Dona Dinda (Desimal: Jurnal Matematika, 2019)
The purpose of this study is to produce linear algebra teaching materials based on Islamic values with a scientific approach to matrix material and a system of linear equations that are appropriate and appropriate to the needs of students. This research method is Research and Development (R & D) with the model used, namely the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, Evaluation. Validation was carried out by material experts, media experts and experts in religious studies and responses from students. The instruments used were in the form of validation questionnaires and student response sheets. Based on the research, the results of material expert validation with a percentage of 84% with the category "Very Worthy", the results of media expert validation with a percentage of 76% with the category "Eligible", the results of the validation of religious experts with a percentage of 76% with the category "Eligible" and after development, material Teachers are implemented or tested to find out student responses with 88% presentation in the "Very Good" category. Based on this research development the advantages of the teaching materials are teaching material related to Islamic values and scientific approaches.